Impact of natural gas consumption on CO2 emissions: Panel data evidence from China's provinces. (20th September 2017) - Dong, Kangyin; Sun, Renjin; Hochman, Gal; Zeng, Xiangang; Li, Hui; Jiang, Hongdian
Abstract: This study utilizes 1995–2014 panel data of the 30 provinces in China to investigate the existence of the environmental Kuznets curve (EKC) for carbon dioxide (CO2 ) emissions in China. The potential impact of natural gas consumption on CO2 emissions is also analyzed. According to the panel fully modified ordinary least squares (FMOLS) and panel dynamic OLS (DOLS) estimation results, in the long run, an inverted U-shaped EKC link exists between per capita CO2 emissions and per capita gross domestic product (GDP). In the panel FMOLS model and panel DOLS model, with 99, 261 yuan and 59, 159 yuan for per capita GDP, the EKC of China will reach its peak by around 2029 or 2019, respectively. Furthermore, natural gas consumption has a significant negative impact on CO2 emissions, which indicates that, 1% increase in natural gas consumption for the panel FMOLS model and panel DOLS model will decrease CO2 emissions by 0.033627% or 0.054914%, respectively. At the provincial level, provinces in which the EKC hypothesis holds are predominantly concentrated in central and eastern China, and the energy consumption structure (share of natural gas in total energy consumption) may affect the occurrence of a significant negative impact of natural gas consumption on CO2 emissions. Another finding of this study is that both the existence of EKC and the occurrence of a positive/negative impact of natural gas consumption on CO2 emissions are independent of the individual provincial per capita GDP. Highlights: The study employs panel FMOLS and panel DOLS estimations to examine the EKC hypothesis with Chinese panel data. The influence of natural gas consumption on CO2 emissions is investigated. A CO2 emissions EKC effect exists in China for the panel. Natural gas consumption has a negative impact on CO2 emissions.